2019
DOI: 10.1016/j.humimm.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HLA-G*01:01:01:04 protects from anti-HLA-class II immunization in pregnant women

Abstract: Factors determining anti-HLA immunization are poorly understood, although anti-HLA immunization following pregnancy is well described. The HLA-G molecule has been extensively described for its implication in immunological tolerance, especially during pregnancy. Transplant studies show an association between HLA-G haplotypes and alloimmunization. Our aim was to investigate the association of HLA-G haplotypes with anti-HLA class I and II immunization in a cohort of women having experienced one or more pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…No HLA Ib genetic polymorphism or IgG4 expression was significantly associated with anti-HLA II immunization, suggesting that anti-HLA I and anti-HLA II immunization may be driven by different factors, as previously suggested ( 31 ). We could not investigate previous published data on the protective role of H03-UTR6-HLA-G*01:01:01:04 on anti-HLA II immunization during pregnancy ( 31 ) as this haplotype was not observed in the cohort under study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…No HLA Ib genetic polymorphism or IgG4 expression was significantly associated with anti-HLA II immunization, suggesting that anti-HLA I and anti-HLA II immunization may be driven by different factors, as previously suggested ( 31 ). We could not investigate previous published data on the protective role of H03-UTR6-HLA-G*01:01:01:04 on anti-HLA II immunization during pregnancy ( 31 ) as this haplotype was not observed in the cohort under study.…”
Section: Discussionsupporting
confidence: 70%
“…Different HLA-G alleles have been associated both to the HLA-G expression level (22)(23)(24)(25)(26) and a better tolerance in pregnancy (27)(28)(29)(30). A previous study on immunization in pregnancy suggested that the HLA-G*01:01:01:04 allele is protective against anti-HLA class II immunization (31).…”
Section: Introductionmentioning
confidence: 99%